GREEN WAREHOUSING INITIATIVES TOWARDS ENVIRONMENTAL SUSTAINABILITY: ADOPTION AND PERFORMANCE IN THE MALAYSIAN FOOD-BASED INDUSTRY - Nitty Hirawaty Kamarulzaman; Hilda Hussin; Amin Mahir Abdullah; Azmawani AbdRahman (UNEJ e-Proceeding, 2012)
Manufacturing industry is reported to be responsible for most of environmental effects because of its operation characteristics. Warehousing as one of the entities in the manufacturing industry supply chain is a place where the unwanted emission normally produced. In many warehouse operations, lighting is one of the biggest facility costs and between 75-90 percent of warehouse operations costs tend to be attributed to lighting.Green initiatives such as introduction of lights with motion sensors and educating employees to turn off lights when not in use can give significant improvement of energy savings up to 50 percent from the total warehouse operations costs. The objectives of this paper are to investigate the level of green warehousing initiatives among Malaysian food-based manufacturers and to measure the performance level of food-based manufacturestowards green initiatives. The finding suggested that the adoption level of Malaysian foodbased manufacturers towards green initiatives in warehousing was categorized as ‘light green’ which implied that these manufacturers have applied environmental practices in their warehousing. The results also indicated that green initiatives in warehousing give significant impacts towards manufacturers’ business performance.